2008
DOI: 10.1002/anie.200801792
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography‐Independent Determination of Ligand Binding Modes

Abstract: Within the last few decades, structure-based drug design (SBDD) has evolved into a powerful tool for the optimization of many low-molecular-weight lead compounds into highly potent drugs.[1] The principle of SBDD lies in the combination of different chemical moieties with the aim of obtaining a molecule that, while possessing the pharmacological properties necessary for a drug, is complementary in shape to the receptor binding pocket. This process requires knowledge of the exact structure of the protein/ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 31 publications
(24 reference statements)
1
55
0
Order By: Relevance
“…Previously, we demonstrated that INPHARMA is able to determine the binding mode of the two ligands L 1 and L 2 to the catalytic subunit of PKA (Orts et al 2008). In this work we aim at establishing INPHARMA as an effective scoring function for binding modes in high-throughput docking campaigns.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we demonstrated that INPHARMA is able to determine the binding mode of the two ligands L 1 and L 2 to the catalytic subunit of PKA (Orts et al 2008). In this work we aim at establishing INPHARMA as an effective scoring function for binding modes in high-throughput docking campaigns.…”
Section: Resultsmentioning
confidence: 99%
“…The INPHARMA data were measured on a mixture of the Chinese hamster Ca catalytic subunit of cyclic adenosine monophosphate (cAMP) dependentent protein kinase A (PKA) (25–30 uM), L 1 (150 uM) and L 2 (450 uM), as described in (Orts et al 2008). The values of the measured INPHARMA NOEs used in this work are in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CORCEMA [46,68,69] and INPHARMA [48,67,72,73] are methods that back predict intra-ligand, intra-protein and protein-ligand NOEs or spin diffusion using the full relaxation matrix formalism. They are powerful tools that can also handle systems undergoing multistate conformational exchange and chemical exchange between the free and bound states.…”
Section: Nmr 2 Versus Other Methods For Rapid Structure Calculations mentioning
confidence: 99%